Takhrīj al-Ḥadīs Digital: Tantangan Epistemologis Penggunaan Basis Data Hadis dalam Verifikasi Riwayat - Agustina, Mery; Siregar, Idris; Bintang , Muhammad Arif Yasin; Masliani, Masliani; Nidaulhaq, Fatiya (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
The development of information technology has driven a significant shift in the practice of hadith retrieval, from manual searches based on classical texts to the use of digital hadith databases that offer speed, accessibility, and ease of search. This shift, while providing methodological efficiency, raises complex epistemological issues, particularly regarding the validity of knowledge, scholarly authority, and the relationship between classical hadith methods and computational logic. This study aims to critically analyze the use of digital hadith databases in the process of narration verification, highlighting the accompanying epistemological implications. The study uses a qualitative-analytical method through an epistemological approach, supported by a review of classical and contemporary literature, as well as a critical analysis of a number of digital hadith platforms widely used in hadith studies. The results of the study indicate a shift in scientific authority from the individual competence of muḥaddith to technological authority that relies on data structures and algorithm design, the limitations of search algorithms in representing the complexity of sanad and matn, the fragmentation of the scientific context of hadith due to the separation of narration from its historical and methodological framework, and the fundamental tension between the evaluative-qualitative epistemology of ʻulūm al-Ḥadīs and the quantitative and reductionist digital logic. These findings confirm that digital hadith databases cannot yet replace the critical function of classical methodology, but rather act as supporting instruments that require a strict epistemological framework. Academically, this study has implications for the need to develop an integrative takhrīj model that synergizes traditional scientific authority with digital technology critically and reflectively in the digital era.